Obtaining magnetic materials from verdazyl radicals via amide bond - Martynko E. А. Ekaterina Andreevna; Petunin P. V. Pavel Vasilievich; Postnikov P. S. Pavel Sergeevich; Trusova M. E. Marina Evgenievna (2017, 2017)
Title screen